Histopathological Changes in the Spleen of Swiss albino Mice after the Combined Exposure of Radiation and Cadmium - Daverey, Jaishree (Asian Journal of Pharmaceutical Research and Development, 2020)
With the technological advancement and diversification of industries, combined with specialization in all fields, the volume and complexity of metals is also increasing day by day. Interaction of metals with other agents is an important aspect as both can interact in a “synergistic” or “additive synergistic” manner, further aggravating the situation. In the present study, combined effect of radiation and cadmium on spleen of mice has been investigated. For the experiment, adult, healthy male Swiss albino mice were exposed to different doses of radiation and also fed with the aqueous solution of CdCl2 which was prepared by dissolving 20 mg of cadmium chloride in 1000 ml of glass distilled water, thus giving a concentration of 20 ppm and then administered orally ad libitum in drinking water continuously, till the end of the experiment. Animals were autopsied by cervical dislocation at each post- interval of 1, 2, 4, 7, 10, 14 and 28 days. Spleen was taken out, weighed, fixed in Bouin’s fluid, dehydrated and embedded in paraffin wax. Transverse sections were cut at 5µ from middle part of the tissue and stained with Harri’s haematoxylin-eosin stain for histopathological studies. Pathological changes after combined exposure in the present investigation depends upon the total dose of radiation provided i.e. higher the dose, higher the damage. Most striking histopathological change in the spleen was loss of lymphoid structure, inflammation, fibrous tissue proliferation, pyknosis, necrosis, karyolysis, karyorrhexis.